The Growth and Yield of Soybean (Glycine max (L.) Merril var. Anjasmoro) in Peat Soil by Giving Liquid Organic Fertilizer (LOF) Banana Stem Kepok (Musa paradisiaca L.) - Amalia Rahman; Zulfa Zakiah; Mukarlina Mukarlina (Universitas Pattimura, 2022)
Soybean cultivation in peatlands in West Kalimantan has constraints, including sour soil conditions and limited nutrients available to plants. The soybean (Glycine max (L.) Merril) variety is one of the leading soybean varieties cultivated in West Kalimantan. Efforts to increase soybean production can be pursued through the application of organic fertilizers in plants. The purpose of this research was to determine the effect of giving liquid organic fertilizer (LOF) from ‘kepok’ banana (Musa paradisiaca L.) stem on the growth and yield of the soybean variety. This study used a Complete Randomized Design (CRD) with 6 treatment levels, namely negative control (without LOF), 50 mL/L, 100 mL/L, 150 mL/L, 200 mL/L, and liquid inorganic fertilizer (positive control). The results showed that the administration of LOF banana stem had a significant effect on the plant height, leaf number, branch number, root fresh weight and shoot fresh weight, root dry weight and shoot dry weight, number of effective root nodules, pod number and pod dry weight. LOF treatment of 150 mL/L gave the best effect on plant height (145.94 cm), leaf number (50.75 stalks), branch number (8.00 branches), shoot fresh weight (156.87 g), shoot dry weight (108.87 g), the effective number of root nodules (35.00 pieces), pod number (92.00 pieces) and pods dry weight (77.72 g).